Perancangan Sensor Suhu Menggunakan Metode Interpolasi Lagrange Berbasis Serat Optik Berstruktur Sms (Singlemode-Multimode-Singlemode) - Aslam Chitami Priawan Siregar; Danang Haryo Sulaksono (Muhammadiyah University, Sidoarjo, 2017)
In this research, a temperature measurement technique was developed using fiber optic structured SMS and OTDR. Where in optical fibers singlemode-multimode-singlemode (SMS) and Optical Time Domain Reflectometer (OTDR) has been widely used for various sensors in detecting damage to the building earlier. Thereafter, calculations are performed using Borland Delphi's Lagrange Interpolation method 7. Characteristics of each of the fiber-optic fiber sensor structures that have been fabricated using multimode optical fibers with lengths of 5.5 cm, 6 cm, 6.5 cm and 7 cm and with use its operating wavelength is 1310 nm. Testing rangesuhusebesar 37oC - 67oC with every temperature rise of 10oC.Berdasarkan research results, multimode length 5.5 cm there is a graph increase with R2 of 93.7%. The increase in temperature, the loss of power generated greater. While the multimode length 6 cm, 6.5 cm, and 7 cm indicate that there is a decrease graph, for multimode length 6 cm with R2 equal to 97,7%, for multimode length 6,5 cm with R2 equal to 99,7%, for long multimode 7 cm with R2 99.2%. While based on result of calculation by Lagrange Interpolation method for suhuberstruktur SMS sensor based on result of calculation using Lagrange Interpolation method with different multimode length have same data regularity compared to temperature sensor structured SMS based on measurement result. For example, as long as 7 cm long multimode yield R2 of 99.2% for the measurement result and yield R2 of 99.3% for the calculation result.